2021
DOI: 10.1101/2021.10.17.464685
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In situ architecture of the ciliary base reveals the stepwise assembly of IFT trains

Abstract: The cilium is an antenna-like organelle that performs numerous cellular functions, including motility, sensing, and signaling. The base of the cilium contains a selective barrier that regulates the entry of large intraflagellar transport (IFT) trains, which carry cargo proteins required for ciliary assembly and maintenance. However, the native architecture of the ciliary base and the process of IFT train assembly remain unresolved. Here, we use in situ cryo-electron tomography to reveal native structures of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Very recently, a combination of cryo‐electron microscopy and expansion microscopy data revealed that IFT trains are assembled around the basal body in Chlamydomonas . [ 43 ] These trains could form exclusively along some triplets of the basal body, according to the associated structural and molecular features mentioned above. Once the kinesin motor gets in action, its processivity would ensure that the trains travel on the doublet where it was assembled.…”
Section: How To Restrict Ift Trains To Some Doublets?mentioning
confidence: 99%
“…Very recently, a combination of cryo‐electron microscopy and expansion microscopy data revealed that IFT trains are assembled around the basal body in Chlamydomonas . [ 43 ] These trains could form exclusively along some triplets of the basal body, according to the associated structural and molecular features mentioned above. Once the kinesin motor gets in action, its processivity would ensure that the trains travel on the doublet where it was assembled.…”
Section: How To Restrict Ift Trains To Some Doublets?mentioning
confidence: 99%
“…While crystal structures have been determined for several IFT-B subunits (2934), no such structures exist for any IFT-A proteins. Recently, cryo-electron tomography (cryo-ET) has provided a valuable in situ view of the assembly of IFT complexes into polymeric structures, known as IFT trains, at the ciliary base, highlighting their stepwise association (35), and capturing snapshots of IFT trains moving along the axonemes (36). These cryo-ET studies have not only revealed the low-resolution structures of the IFT-A and IFT-B complexes, but also revealed their cellular context, the mode of IFT-A/IFT-B associations, and the stoichiometries between the complexes.…”
Section: Introductionmentioning
confidence: 99%